Exploring the Dynamics of CPO Spot and Futures Prices in Relation to Global Crude Oil Price: Evidence from India using ARDL Model Approach and Granger Causality Tests - Supriya R; Rajesh Mamilla (Qubahan Academic Journal)
This study examines the connection between Crude Palm Oil (CPO) spot and futures prices, and global crude oil prices using ARDL model and Granger causality tests to analyze data collected between January 2011 and April 2022, including CPO spot and futures prices, MCX, and WTI Crude oil futures. The results from the coefficient estimations show that both CPO future price percentage changes and crude oil price have a statistically significant impact on the CPO spot price. The study also reveals a long-term relationship between the dependent and independent variables in the level’s comparison. The study also demonstrates that global crude oil prices can significantly influence the spot and futures prices of CPO. This research provides useful insight for stakeholders in the palm oil industry, policymakers, and investors.